(untitled) (Journal of Oriental Studies, 2018)
The presented article has been designed for the purpose of carrying out a comparative analysis of the similarities and differences between the dialectological units of the genetically and typologically kindred Turkic languages and of lexical-semantic and morphological features of these units. Our primary goal is to describe and analyze these language units in those languages, to systematically explain the role of historical and social linguistic factors and ethnocultural indications in their formation and to learn the typological character of the patterns. The presented article is a step taken for development of the Turkic linguistics